Buku Interaktif IPAS berbasis QR Code untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas V SD - Budiastini, Ni Putu Putri; Ketut Suma; Widiana, I Wayan (Universitas Pendidikan Ganesha, 2025)
The low level of students’ critical thinking skills remains an unresolved issue due to the suboptimal application of innovative learning strategies and the limited use of instructional media specifically designed to enhance higher-order thinking. This study aimed to develop, validate, and evaluate the practicality and effectiveness of an Interactive Science and Social Studies (IPAS) Book based on QR Codes to enhance elementary students’ critical thinking skills. This research employed a development approach by adapting the 4D model (define, design, develop, disseminate). The participants included three experts for content, media, and language validation; nine students with high, medium, and low abilities for the practicality test; and thirty students as the sample for the effectiveness test. Data were collected through questionnaires and critical thinking skill tests, then analyzed using both quantitative and qualitative approaches. The results revealed that the developed product was (1) valid, with a Content Validity Index (CVI) of 1.00; (2) practical, with a practicality score of 73%; and (3) effective, based on a Wilcoxon test result of 0.000 (p < 0.05). In conclusion, the QR Code-based Interactive IPAS Book is proven to be valid, practical, and effective in enhancing elementary students’ critical thinking skills and holds potential for broader implementation in classroom learning.